Universal Solution Synthesis of Sulfide Solid Electrolytes Using Alkahest for All‐Solid‐State Batteries. Issue 16 (13th March 2022) - Lee, Ji Eun; Park, Kern‐Ho; Kim, Jin Chul; Wi, Tae‐Ung; Ha, A. Reum; Song, Yong Bae; Oh, Dae Yang; Woo, Jehoon; Kweon, Seong Hyeon; Yeom, Su Jeong; Cho, Woosuk; Kim, KyungSu; et al.
Abstract: The wet‐chemical processability of sulfide solid electrolytes (SEs) provides intriguing opportunities for all‐solid‐state batteries. Thus far, sulfide SEs are wet‐prepared either from solid precursors suspended in solvents (suspension synthesis) or from homogeneous solutions using SEs (solution process) with restricted composition spaces. Here, a universal solution synthesis method for preparing sulfide SEs from precursors, not only Li2 S, P2 S5, LiCl, and Na2 S, but also metal sulfides (e.g., GeS2 and SnS2 ), fully dissolved in an alkahest: a mixture solvent of 1, 2‐ethylenediamine (EDA) and 1, 2‐ethanedithiol (EDT) (or ethanethiol). Raman spectroscopy and theoretical calculations reveal that the exceptional dissolving power of EDA–EDT toward GeS2 is due to the nucleophilicity of the thiolate anions that is strong enough to dissociate the GeS bonds. Solution‐synthesized Li10 GeP2 S12, Li6 PS5 Cl, and Na11 Sn2 PS12 exhibit high ionic conductivities (0.74, 1.3, and 0.10 mS cm −1 at 30 °C, respectively), and their application for all‐solid‐state batteries is successfully demonstrated. Abstract : The universal solution synthesis of sulfide solid electrolytes is first demonstrated. The alkahest solvent, 1, 2‐ethylenediamine–1, 2‐ethanedithiol, fully dissolves not only Li2 S (or Na2 S), P2 S5, and LiCl, but also metal sulfides (e.g., GeS2 and SnS2 ), forming homogeneous solid electrolyte solutions. Solution‐synthesized Li10 GeP2 S12, Li6 PS5 Cl, and Na11 Sn2 PS12 exhibit high ionic conductivities, and their applicability to all‐solid‐state batteries is successfully demonstrated.